Effect of radiocontrast media on kidneys of patients with renal disease. Issue 6271 (11th April 1981) - Rahimi, A; Edmondson, R P; Jones, N F
Abstract : A prospective study was undertaken of 15 patients with impaired renal function undergoing x-ray procedures entailing the use of contrast material to see whether any deterioration in renal function resulted. Patients with diabetes or myelomatosis were excluded. Detailed observations were made during three days before and after the x-ray procedure to detect any change in factors such as fluid state, drug treatment, infection, or diet which might have affected renal function. No significant changes occurred in endogenous creatinine and 51Cr-EDTA clearances, or in plasma creatinine and urea concentrations after the x-ray procedures. Furthermore, there was no change in urinary activity of N-acetyl-beta-D-glucosaminidase, which is a highly sensitive indicator of renal parenchymal damage. Provided that fluid depletion and multiple x-ray procedures with radiocontrast material in rapid sequence are avoided, these procedures do not appear to affect renal function adversely, even when renal disease is advanced.